1998
DOI: 10.1074/jbc.273.28.17343
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Setting for the Sorting Motifs Present in the Adenovirus E3-13.7 Protein Which Down-regulates the Epidermal Growth Factor Receptor

Abstract: The adenovirus E3-13.7 protein interferes with endosomal protein sorting to down-regulate the epidermal growth factor receptor and related tyrosine kinase receptors. The cytoplasmic C terminus of this protein contains three protein sorting motifs which are related to the function of E3-13.7. In this study, the structure of a 23-residue polypeptide corresponding to this domain was examined using solution NMR and CD spectroscopic methods. The peptide was observed to exist in a mostly random structural state in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The side-chains of the two key leucine residues are largely buried in the micelle surface. We have reported previously that the corresponding LL sequence in the E3-13.7 protein exhibits similar micellebinding and helical properties (Vinogradova et al, 1998). Interestingly, the 679-LL-stabilized helical structure represented in Fig.…”
Section: Fig 4 (A)mentioning
confidence: 87%
See 1 more Smart Citation
“…The side-chains of the two key leucine residues are largely buried in the micelle surface. We have reported previously that the corresponding LL sequence in the E3-13.7 protein exhibits similar micellebinding and helical properties (Vinogradova et al, 1998). Interestingly, the 679-LL-stabilized helical structure represented in Fig.…”
Section: Fig 4 (A)mentioning
confidence: 87%
“…The adenovirus protein diverts receptors in a basal internalization-recycling pathway to MVB internal vesicles without activating EGFR or increasing its internalization rate (Hoffman and Carlin, 1994;Hoffman et al, 1992b). Interestingly, E3-13.7 has an exact copy of a five amino acid sequence including 679-LL found in EGFR that is required for its biological activity (Table 1c), suggesting E3-13.7 can support a normal cellular function (Carlin et al, 1989;Crooks et al, 2000;Hoffman et al, 1992a;Vinogradova et al, 1998). Thus, E3-13.7 provides a novel model for studying the molecular basis of EGFR sorting to lysosomes without ligand-induced saturation of this transport pathway (Piper and Luzio, 2001;Wiley and Burke, 2001).…”
mentioning
confidence: 99%
“…The disappearance of specific peaks has previously been observed in dynamic regions of globular proteins (31), when intermediate conformational exchange results in significant broadening of the spectra, often beyond the experimental detection. In addition to conformational exchange, temperature increase in partially disordered systems (32) stimulates exchange between non-protected amides and water protons, resulting in further broadening of the spectra. We have embedded L1-CT in dodecylphosphocholine (DPC) micelles to mimic the interactions with membrane surface, which could enforce and stabilize the structural rearrangements in otherwise unstructured cytoplasmic tails of integral membrane proteins (33).…”
Section: L1-ct In Aqueous Solutionmentioning
confidence: 99%
“…2) are highlighted in gray or black, respectively. Nuclear magnetic resonance studies have shown that residues 87-LLRIL comprise an amphipathic helix stabilized by interactions with membrane mimetic micelles (45). Two additional residues are presented in the exocytic loop connecting the two membrane spanning helices: Ala23, comprising the amino terminus of the 11.3-kDa cleaved form of the protein produced cotranslationally by signal peptidase, and Cys31, which forms intermolecular disulfide bonds (27).…”
Section: Resultsmentioning
confidence: 99%